2012
DOI: 10.2139/ssrn.2221038
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Accept Equals Willingness to Pay for Labor Market Estimates of the Value of Statistical Life

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Kniesner, Viscusi, and Ziliak presented empirical estimates which indicate that there is no significant difference in VSL levels whether workers who change jobs are incurring increases in risk or obtaining decreases in risk, because the wage-risk tradeoffs are similar irrespective of the direction of change in the worker's job risk. 13 These results provide a test of the general theoretical underpinnings of the VSL analysis, namely, that the tradeoff rates between wages and changes in risk should be the same for small changes of risk levels in each direction.…”
Section: Use Of the Cfoi With Panel Datamentioning
confidence: 92%
“…Kniesner, Viscusi, and Ziliak presented empirical estimates which indicate that there is no significant difference in VSL levels whether workers who change jobs are incurring increases in risk or obtaining decreases in risk, because the wage-risk tradeoffs are similar irrespective of the direction of change in the worker's job risk. 13 These results provide a test of the general theoretical underpinnings of the VSL analysis, namely, that the tradeoff rates between wages and changes in risk should be the same for small changes of risk levels in each direction.…”
Section: Use Of the Cfoi With Panel Datamentioning
confidence: 92%
“…16 The discrepancy they find between WTP and WTA arises because their WTA estimates are even larger. As further support for the reasonableness of the $5-$12 million range, many estimates of willingness to pay for safety equipment and safer cars, clearly WTP and not WTA, also fall in this range after adjustment to the 2010 price level, although toward the lower end.…”
mentioning
confidence: 97%
“…16 In the paper they report regressions for job changers moving to riskier jobs, who should be deciding on the basis of WTA, and those moving to less risky jobs, who should be deciding on the basis of WTP. Their point estimates of the compensating wage differentials for the 2 groups are similar in some specifications, different in others, with WTA usually but not always greater than WTP, but the differences are not large.…”
mentioning
confidence: 99%
“…Theoretically, there was little difference between the 2 values (Willig 1976;Randall and Stoll 1980). The WTA/WTP ratio for nonmarket goods was shown to be the highest of various goods (Horowitz and McConnell 2002;Kniesner et al 2014). Horowitz and McConnell (2002) reviewed 45 surveys and found that WTA was larger than WTP with an average multiple of 2 to 10 times, the average proportion was 7.17, and the lowest was 0.74 and the highest 112.67.…”
Section: The Statistical Distribution Of Cvm Valuesmentioning
confidence: 99%